Maximum strength-power-performance relationships in collegiate throwers - Stone, M. H.; Sanborn, K.; O'Bryant, H. S.; Hartman, M.; Stone, M. E.; Proulx, C.; Ward, B.; Hruby, J. (The Journal of Strength and Conditioning Research, 2003)
Presently the degree to which peak force influences power production or explosive performance such as strength training movements or throwing (shot-put and weight-throw) is unclear. This study describes the relationships between a measure of maximum strength, isometric peak force (IPF), dynamic peak force (PF), peak power (PP), the 1-repetition movement power snatch (SN), and throwing ability over an 8-week training period. Five male and 6 female (n = 11) well-trained collegiate throwers participated. PF was measured using an AMTI force plate; PP was measured using an infrared-ultrasonic tracking device (V-Scope, Lipman Electronics). Clean pulls from the midthigh position were assessed isometrically and dynamically at a constant load, 30% and 60% of IPF. Specific explosive strength was evaluated using an SN and using the shot-put (SP) and weight-throw (WGT) measured under meet conditions. Variables (PF, PP, SN) were assessed 3 times at 0 weeks, 4 weeks, and 8 weeks. Each measurement period preceded a field meet by 3 days. Peak force, peak rate of force development, and PP increased over the 8 weeks. Correlation coefficients (r) indicate that IPF is strongly related to dynamic PF and PP 30%, 60% of the IPF. Furthermore, strong correlations were found for the SN and the distance for the SP and WGT, and these relationships tended to increase over time. Results suggest that maximum strength (i.e., IPF) is strongly associated with dynamic PF. In addition, maximum strength is strongly associated with PP even at relatively light loads such as those associated with sport-specific dynamic explosiveness (i.e., SN, SP, WGT).